2021
DOI: 10.1038/s42003-021-02203-0
|View full text |Cite
|
Sign up to set email alerts
|

The chaperonin CCT8 controls proteostasis essential for T cell maturation, selection, and function

Abstract: T cells rely for their development and function on the correct folding and turnover of proteins generated in response to a broad range of molecular cues. In the absence of the eukaryotic type II chaperonin complex, CCT, T cell activation induced changes in the proteome are compromised including the formation of nuclear actin filaments and the formation of a normal cell stress response. Consequently, thymocyte maturation and selection, and T cell homeostatic maintenance and receptor-mediated activation are seve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 76 publications
(87 reference statements)
0
9
0
Order By: Relevance
“…Bergithe’s studies had shown that Th2 cell polarization and T-cell metabolism are dependent on CCT8 expression, 32 but no research has reported the effect of CCT8 on tumor-infiltrating lymphocytes (TILs). Our study firstly demonstrated that CCT8 expression was positively correlated with CD4+ Th2 cell infiltration in the vast majority of TCGA cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Bergithe’s studies had shown that Th2 cell polarization and T-cell metabolism are dependent on CCT8 expression, 32 but no research has reported the effect of CCT8 on tumor-infiltrating lymphocytes (TILs). Our study firstly demonstrated that CCT8 expression was positively correlated with CD4+ Th2 cell infiltration in the vast majority of TCGA cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Folding of actin by CCT/TriC is another distinguished mechanism identi ed to be activated in CeD patients. CCT/TriC, as a molecular chaperone, is involved in the proper folding of up to 10% of newly synthesized proteins, including cytoskeleton components (21,22). Interestingly, actin as a major component of the cytoskeleton has been related to autoin ammatory diseases through the formation of misfolded structures (23).…”
Section: Discussionmentioning
confidence: 99%
“…CCT8 is a circRNA and is a member of the TCP-1 chaperone protein (CCT) family of genes. The chaperonin CCT8 controls proteostasis essential for T cell maturation, selection, and function ( Oftedal et al, 2021 ). Current studies have found that CCT8 was overexpressed in cancer, but no study so far has reported any association of CCT8 with asthma.…”
Section: Discussionmentioning
confidence: 99%